2022
DOI: 10.3748/wjg.v28.i27.3282
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B and circadian rhythm of the liver

Abstract: The circadian rhythm in humans is determined by the central clock located in the hypothalamus’s suprachiasmatic nucleus, and it synchronizes the peripheral clocks in other tissues. Circadian clock genes and clock-controlled genes exist in almost all cell types. They have an essential role in many physiological processes, including lipid metabolism in the liver, regulation of the immune system, and the severity of infections. In addition, circadian rhythm genes can stimulate the immune response of host cells to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 120 publications
(210 reference statements)
0
2
0
Order By: Relevance
“…Studies have shown that an increasing number of diagnosed cases of hepatocellular carcinoma are thought to be related to circadian clock disorders, obesity and non-alcoholic fatty liver disease ( Crespo et al, 2021 ). The occurrence and progression of liver cancer relies on multiple molecular mechanisms, involving genetic and epigenetic alterations of oncogenes and tumor suppressor genes, as well as disorder control, abnormal functions and inappropriate interactions of key molecular cascades such as Hedgehog, MAPK and PI3K/AKT/mTOR signaling pathways ( Skrlec and Talapko, 2022 ). Studies have reported that decreased levels of melatonin or decreased excretion of its main metabolite, 6-thiooxidative melatonin, are associated with an increased risk of cancer, suggesting the anticancer effects of this indoleamine.…”
Section: Effects Of the Circadian Clock On Biological Processes After...mentioning
confidence: 99%
“…Studies have shown that an increasing number of diagnosed cases of hepatocellular carcinoma are thought to be related to circadian clock disorders, obesity and non-alcoholic fatty liver disease ( Crespo et al, 2021 ). The occurrence and progression of liver cancer relies on multiple molecular mechanisms, involving genetic and epigenetic alterations of oncogenes and tumor suppressor genes, as well as disorder control, abnormal functions and inappropriate interactions of key molecular cascades such as Hedgehog, MAPK and PI3K/AKT/mTOR signaling pathways ( Skrlec and Talapko, 2022 ). Studies have reported that decreased levels of melatonin or decreased excretion of its main metabolite, 6-thiooxidative melatonin, are associated with an increased risk of cancer, suggesting the anticancer effects of this indoleamine.…”
Section: Effects Of the Circadian Clock On Biological Processes After...mentioning
confidence: 99%
“…Among the core clock components, REV-ERB regulates HBV and HDV particle entry, and Bmal1 directly binds to HBV DNA, increasing the activity of the HBV promoter activity and thus promoting the production of viral particles in the liver. 12 , 13 On the contrary, Bmal1 depletion inhibits the replication of the HCV via disturbing the lipid signalling pathways. 14 …”
Section: Introductionmentioning
confidence: 99%